Człowiek w obrazie miasta - aktor drugiego planu? = Man in the city image - a background actor? - Nyćkowiak, Justyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The lack of integrity between administrative defining of urban space and the meaning ascribed to it by the inhabitants is one of the traditional yet most up-to-date problems considered on sociologial grounds. The goal of this article is the reconstrution of the administrative process of the transformation of urban space, and particularly the diagnosis of the possibilities of the participation of its very occupants in it.
Keywords: miasto; człowiek; przestrzeń miejska; socjologia